COMPARING DIFFERENT STRATEGIES IN REDUCING THE ECONOMIC IMPACT OF RECESSIVE GENETIC DISORDERS AFFECTING REPRODUCTIVE EFFICIENCY IN DAIRY CATTLE: A SIMULATION STUDY - F. Salimi; A. N. Javaremi2; M. Aminafshar1and M. Honarvar (Journal of Animal and Plant Sciences, 2014)
The objective of this study was to describe changing pattern in frequency of carriers of lethal haplotypes over time under different scenarios and to estimate of economic loss resulting from carrier by carrier matings in dairy cattle population. Three scenarios were developed.In the first scenario, the mating of a pair of two carriers of the same lethal haplotype was avoided. In the second scenario, there was no interference for matings between carrier animals. In the third scenario, all carrier bulls were eliminated from the population. In first scenario, frequency of carriers reduced slowly from 0.67 in year 1 to 0.56 in year 25. In the second scenario, frequency remained almost constant and showed insignificant decrease. In the third scenario, frequency of carriers reduced from 0.68 in year 1 to 0.14 in year 25. Less genetic progress was achieved for scenario 3 compared with other two scenarios. A significant difference was observed between animals in scenario 2 and those in scenario 1 (P<0.002); and between animals in scenario 2 and those in scenario 3 (P<0.002) for days open. Total economic losses resulting from mating between carriers ranged from $45248 to $59045, on average for 2074 matings per year.
Keywords: lethal recessive; haplotype; dairy cattle; pregnancy losses